Designing a Model of Consumer Purchase Behavior towards Domestic Brands of Sports Apparel - Yaser Ahmadi; Zahra Sadat Mirzazadeh; Seyyed Morteza Azimzadeh (The Society of Aging and Physical Activity (SAPA), 2016)
Iran's apparel market is currently filled with foreign brands that are generally ranked as high quality goods with high prices. With a surface examination of the apparel market and customers’ opinions, it can be concluded that Iranian apparel, despite having lower prices, is not in a suitable status in comparison with its foreign counterparts. Accordingly, the purpose of this paper is to explore the impact of individual characteristics and brand-specific features, and finally design a model of consumer purchase behavior towards domestic brands of sports apparel that are available in the Iran market. The method of this study is descriptive-correlational and in terms of the aim, is applicable. The statistical population of the study consisted of sports experts. 141 individuals as sample size were studied out of 220 individuals of the population. A questionnaire used by Kumar, Kim, and Pelton (2009) was also used to collect the data, and the validity of the model and the relationship between the studied variables was supported by the techniques of structural equation modeling. The research findings showed that self-concept of individuals has no role in their orientation towards domestic brands of sports apparel, but need for uniqueness was effective on individual’s orientation towards brand. On the other hand, brand orientation also had positive impact on both emotional value and perceived quality of domestic brands of sports apparel. Also, according to the findings, increasing brand orientation did not increase their purchase intention. All the dimensions of brand in this study, both perceived quality and emotional value had significant positive impact on consumer’s purchase intention towards domestic brands of sports apparel.